Electives Shopping, Grading Policies and Grading Competition. (9th December 2020) - Gregor, Martin
Abstract : This paper analyses grading competition between instructors of elective courses when students shop for high course scores, the instructors maximize class size, and the school imposes a ceiling on mean course scores to limit grade inflation. We demonstrate that curriculum flexibility (more listed courses or fewer required courses) intensifies the competition: in particular, top scores increase. To tame incentives to provide large scores, we suppose that the school additionally introduces a top‐score grading policy. We consider three regimes. First, the school caps top scores. Then grading competition segregates students into a concentrated group of achievers and a dispersed group of laggards. This effect extends to constraints on scores at lower quantiles. Second, the school normalizes the range of scores by adjusting the mean‐score ceiling. On normalization, scores of a less flexible curriculum first‐order stochastically dominate scores of a more flexible curriculum. Hence all students prefer rigid curricula. Third, the school requires that the mean score is evaluated for enrolled students instead of a representative sample of students. Then the instructors stop competing for students, which introduces assortative inefficiencies. Overall, we show that addressing grade inflation through grading policies may generate inequalities, rigidities and inefficiencies.